Traffic light system regulation of induced seismicity under multi-well fluid injection - Miao He; Qi Li; Xiaying Li; Yao Zhang (Energy Geoscience)
The occurrence time and magnitude of injection-induced seismicity are influenced by engineering factors, such as wellhead pressure, injection location, injection volume, and injection rate. Understanding the relationship between injection operations and seismic magnitude is of great significance for optimizing industrial production and reducing earthquake disasters. Numerical simulation of hydro-mechanical coupling is a crucial method for studying injection-induced seismicity. However, few studies have explored the risk management measures for injection-induced seismicity from the perspective of engineering. How seismic magnitudes can be reduced through reasonable adjustments to injection operations in engineering remains unclear. Therefore, in this study, a 3D hydro-mechanical coupling model involving multiple faults and injection wells was established based on the geological background and well location of Fox Creek, Canada. Different injection schemes under multi-well and multi-fault conditions were studied, and a traffic light system was used to simulate and control the magnitudes under a multi-well injection scheme. Specifically, we simulated injection scenarios involving up to three wells and analyzed the response of five faults. We compared the maximum moment magnitude of different scenarios by controlling the same injection volume. The results revealed the effect and advantage of the multi-well scheme in reducing seismic magnitude. To reduce the risk of induced seismicity, utilizing far-fault operational wells to compensate for the effects of near-fault operational wells proves to be an efficient and cost-effective method, with potential for wide practical applications.